Application of Nano Drugs in Treatment of Leishmaniasis - Seyed Hossein Shahcheraghi; Jamshid Ayatollahi; Marzieh Lotfi; Ali Fattahi Bafghi; Seyed Hossein Khaleghinejad (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2016)
Objective: Leishmaniasis is endemic in 88 countries with incidence rate of 1.5-2 million; the most common form of leishmaniasis is cutaneous leishmaniasis (CL) with 1.5 million new cases per year. Correct diagnosis and characterization of the particular parasite is important for evaluating prognosis and prescribing appropriate treatment. The current management of leishmaniasis is drug treatment of patients, to alleviate disease and vector control to reduce its transmission. Also, current treatments for visceral leishmaniasis are unsatisfactory because of their toxicity, resistance and high cost. The purpose of the present study was to review the application of nano drugs in treatment of leishmaniasis. Materials and Methods: it was used as source of research the following databases: MEDLINE, Cochrane Library, Scielo, PubMed and the database of CAPES. Results: It has been proved nanosilver particles with highly small sizes, have a good penetration into the cutaneous lesions and a good efficacy on leishmaniasis.